Smooth null hypersurfaces near the horizon in the presence of tails - Kozameh, Carlos Nicolas (2013)
We show that the power-law decay modes found in linear perturbations of Schwarzschild black holes, generally called tails, do not produce caustics on a naturally defined family of null surfaces in the neighbourhood of i+ of a black hole horizon. This null congruence thus yields a well behaved coordinate system both near the event horizon and at null infinity.